Peran Artificial Intelligence dalam Transformasi Komunikasi Interpersonal: Peluang dan Tantangan di Era Digital - Riyadi; Pramudita Budi Rahayu; Hafied Cangara (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
This study explores the transformative role of Artificial Intelligence (AI) in interpersonal communication, focusing on the opportunities and challenges in the digital era. Through a comprehensive literature review, we examine how AI technologies such as virtual assistants, chatbots, and predictive algorithms are reshaping the landscape of personal interactions. The research highlights AI's potential in enhancing communication efficiency, personalization, and accessibility, while also addressing critical challenges including the loss of emotional depth, user frustration, and authenticity issues. Furthermore, the study delves into ethical considerations surrounding AI-mediated communication, particularly privacy concerns, technological dependence, and the creation of filter bubbles. Our findings suggest that while AI offers unprecedented opportunities for streamlined and personalized communication, it also poses significant challenges to the emotional and ethical dimensions of interpersonal relationships. This research contributes to the growing body of knowledge on human-AI interaction and provides insights for developing more balanced and ethical approaches to integrating AI in everyday communication.